The intergenerational health, social care, and justice system contacts associated with household substance misuse in Wales - Evans, Hywel; Farr, Ian; Bailey, Grace; Davies, Gareth; Dixon, Josh; Fallick, Sam; Maimaris, Joanne; Ohaeri, Columbus; Oluwasuji, Olabambo; Phillips, Ryan; Skermer, Matthew; James, Delyth; et al. (International Journal of Population Data Science, 2026)
Background Household substance misuse (SM) is associated with child deprivation and worse physical and mental health. This study utilised linked healthcare, justice, and children's social care data in Wales for the first time, to create a reusable cohort of households that experience substance misuse (SMHH). Methods Using the SAIL Databank, a population-scale retrospective electronic cohort (e-cohort) was created to perform a cross-sectional analysis of SM-related health and criminal justice events during 2011-2019 for adults and children in SMHH, which were compared with the rest of the population using period prevalence ratios (PR) and 95% confidence intervals (CI). Other variables included demographics, children's social care, healthcare, and SM-related criminal court cases. Results There were 776,366 children and 1,032,088 adults, where 83,558 children (11%) lived in SMHH, and 48,398 (5%) of adults who lived with a child had a SM event. Children in SMHH had a 133% higher prevalence of referral to SM treatment (PR = 2.33, CI: 2.23-2.43), and a SM-related criminal case was 42% more prevalent (PR = 1.42, CI: 1.30-1.55) during the period. Notably, the prevalence of SMHH children receiving care and support was 300% higher (PR = 4.00, CI: 3.92-4.08), and self-harm was 78% more prevalent (PR = 1.78, CI: 1.71-1.86). Conclusion SMHH children experience significant disparities, including higher deprivation, adverse birth outcomes, mental health issues, social care involvement, and SM-related criminal justice prosecutions. Evidence-based interventions and policy are needed to support adults and children in SMHH to mitigate the intergenerational impact.